"All Power to the Imagination!": A Leftist Critique of Bureaucratic Violence,Technologies and RationalityBook Review: Graeber D. 2015. The Utopia of Rules: On Technology, Stupidity,and the Secret Joys of Bureaucracy. New York: Melville House - Gudova, Elena (Journal of Economic Sociology, 2015)
In the preface to The Utopia of Rules, David Graeber states that his book does not attempt to build up a new theoretical approach to bureaucracy but it is rather an essay collection with a focus on three bureaucratic features: violence, technology and rationality. However, the cornerstone of bureaucracy seems to rest on both unexpected and anticipated effects of creativity and imagination, whether related to the work of government officials and origins of sovereignty, force fields and contemporary science development, or superheroes and comic book history. Graeber not only illustrates why our life has been organized around filling out forms (p. 44), but gives it a wider scale through an anthropological understanding of bureaucratic practices and technologies. The interesting thing is that he never gives a precise definition of what bureaucracy really is and where we can find it, but in the disenchanted modernity and modern capitalist economy it seems to be omnipresent. The book is divided into four thematic parts: the first is the structural violence and deliberate stupidity of bureaucratic institutions; the second questions scientific development and claims that we have moved from poetic to bureaucratic technologies; the third one is rationality and playfulness and their relation to human nature; and the last one (in an Appendix) considers the link between creativity and violence and the role of bureaucracy in it.